2023
DOI: 10.1007/s12144-023-04642-w
|View full text |Cite
|
Sign up to set email alerts
|

When suffering contradicts belief: measuring theodical struggling

Abstract: Global meaning systems help people make sense of their experiences, but suffering can violate global meaning and create distress. One type of potential violation is conflict between one’s experience of suffering and one’s deeply-held beliefs about God as loving, powerful, and just. The problem of theodicy—why an all-powerful and all-loving God would allow suffering—has long been an important theological and philosophical concern, but little is known about how theodicy plays out psychologically for religious in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Although spirituality and religiosity are generally positive predictors of subjective well-being (Villani et al, 2019) and can play an important role in physical health (Koenig et al, 2012), it is also well-known that many people report various "religious/spiritual struggles." These are defined as tensions, strains, or conflicts relative to what people hold sacred (Exline, 2013;Lukoff et al, 1998;Pargament et al, 2005;Pargament & Exline, 2021;Park et al, 2023). However, there are ongoing questions about the nature or factor structure of such struggles.…”
Section: Focus Area B: Sources Of Negative Contents In Religio-spirit...mentioning
confidence: 99%
“…Although spirituality and religiosity are generally positive predictors of subjective well-being (Villani et al, 2019) and can play an important role in physical health (Koenig et al, 2012), it is also well-known that many people report various "religious/spiritual struggles." These are defined as tensions, strains, or conflicts relative to what people hold sacred (Exline, 2013;Lukoff et al, 1998;Pargament et al, 2005;Pargament & Exline, 2021;Park et al, 2023). However, there are ongoing questions about the nature or factor structure of such struggles.…”
Section: Focus Area B: Sources Of Negative Contents In Religio-spirit...mentioning
confidence: 99%
“…People for whom religion has played a central role in shaping their global beliefs are likely to rely on the religious system to appraise the meaning of the traumatic event [ 35 ]. Indeed, studies are continuously using Park's model as a relevant and viable framework for investigating how individuals and societies, including Muslim populations, cope with life's adversities [ 7 , 22 , 34 , [36] , [37] , [38] , [39] , [40] ]. For instance, in a study conducted among Muslim cancer patients, it was reported that meaning-making, as presented in Park's model, created a more positive outlook, by helping these cancer patients find new goals in life [ 7 ].…”
Section: A Review Of the Literaturementioning
confidence: 99%